Development of a Procurement Information System for Medical Service Providers - Almas Agung Firdaus; Abdul Rezha Efrat Najaf; Tri Luhur Indayanti Sugata (bit-Tech, 2025)
Procurement processes in healthcare institutions often face challenges such as delays, lack of documentation, and limited transparency in vendor selection. These issues can negatively impact the operational efficiency and availability of medical logistics. This study aims to develop a web-based procurement information system that addresses these problems through a structured digital approach. The research was conducted using a case study at Sekata Medical Center Clinic in Samarinda. The system was developed using the Waterfall model, which includes five stages: requirements analysis, system design, implementation, testing, and maintenance. The development was carried out using PHP as the programming language and MySQL as the database, supporting multiple user roles including admin, department, division, and vendor. The system implementation includes key features such as item request submission, vendor selection, invoice processing, and goods verification. Testing using the Black Box method confirmed that all functionalities performed correctly according to the defined specifications, with accurate error handling and validation processes. The results demonstrate that the system enhances the procurement process by providing structured workflows, real-time documentation, and transparency across all stages. In conclusion, this research contributes to improving procurement efficiency, data accuracy, and accountability in medical service providers. It also lays the groundwork for future development, such as integration with real-time reporting, enhanced data security, and broader deployment in other healthcare institutions.